GROSS MOTOR STIMULATION THROUGH EDUCATIONAL NEUROSCIENCE-BASED ACTIVITY BOOKS TO IMPROVE BRAIN DEVELOPMENT IN EARLY CHILDREN PAUD SIERA PERTIWI DEPOK WEST JAVA - jodi christina (International Conferences on Early Childhood Education Proceedings, 2023)
Brain development in early childhood is an important stage in laying the foundation for cognitive, emotional and motor skills in the future. Gross motor stimulation is an important aspect in optimizing children's brain development. Previous research has shown that teaching methods related to educational neuroscience can accelerate and strengthen a child's brain learning. This study aimed to identify the potential use of educational neuroscience-based activity books as an effective motor stimulation tool in early childhood. This study used a qualitative approach consisting of aged children 4-6 years with their parents. The motor skills of the children in this intervention improved compared to the control group that did not receive the intervention. In addition, parents also reported positive changes in their child's behavior and motor skills after using this activity book. This study shows that the use of neuroscience educational activity books can be an effective strategy for increasing gross motor stimulation and brain development in early childhood. The results of this research can help develop more effective learning methods that focus on motor stimulation in early childhood. It is hoped that this research can provide a basis for further development of the use of pedagogical neuroscience in early childhood education.